Counseling on Communication Ethics Through Electronic Media to the Saham Longhouse Community in Landak Regency - Gatot Yuliana; Regina Regina; Sudarsono Sudarsono; Ikhsanudin Ikhsanudin; Clarry Sada; Dwi Riyanti; Y. Touvan Juni Samodra (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2023)
The community service entitled